Perception of Scientists and Journalists on the Dissemination of Science and Technology Issues in Chile [Percepción de Los Científicos y Periodistas Sobre la Divulgación de la Ciencia y la Tecnología en Chile] - Broitman-Rojas, C (University of La Laguna, 2017)
Introduction: This article shows the perception of Chilean scientists and journalists in relation to the dissemination of science and technology issues in the media. Methodology: As a layout, it was held a query addressed to Chilean scientists (n=139), which was triangulated with three journalistic research studies to further validate its outcomes. Results and conclusions: As a conclusion, the results show that scientists consider that the dissemination of science issues in the media in Chile is poor in quality and the reasons for not being highly present in the media are based on the lack of effective public policies, interest of the media or the lack of professional networks that might increase the visibility of the topic news. However, 84.2% of respondents have given an interview sometime. A controversial finding - in both groups of professionals- is to consider that journalists use insufficient scientific language in relation to what the population requires. It is essential to develop public policies with specific indicators for the dissemination of science and scientific journalists need to do some serious reflections on the matter. © 2017, University of La Laguna. All rights reserved.